2016
DOI: 10.1371/journal.pone.0149970
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Coverage Surveys and Linked Biomarker Serosurveys in Three Regions in Ethiopia

Abstract: ObjectiveDemographic and health surveys, immunization coverage surveys and administrative data often divergently estimate vaccination coverage, which hinders pinpointing districts where immunization services require strengthening. We assayed vaccination coverage in three regions in Ethiopia by coverage surveys and linked serosurveys.MethodsHouseholds with children aged 12–23 (N = 300) or 6–8 months (N = 100) in each of three districts (woredas) were randomly selected for immunization coverage surveys (inspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 32 publications
(44 reference statements)
1
41
0
Order By: Relevance
“… Prioritizing and coordinating micronutrient intervention programs Deficiencies in micronutrients contribute to excessive morbidity and mortality of young children globally 13 Travassos MA. et al [ 24 ] 2016 Ethiopia Immunization tetanus Haemophilus influenzae type b (Hib) Normative children aged 12–23 or 6–8 months Administrative Data vaccination cards and immunization clinic records household survey maternal recall Biomarkers Serosurveys Conflict in coverage rate of different sources 14 Ríos-Blancas MJ. et al 2016 Mexico Hypertension treatment The prevalence of hypertension Physical examination in national health survey biomarkers self-report of antihypertensive treatment Statistical methods two-step least squares method (MC2E) was used using instrumental variables (VI) instrumental variables One of leading causes of death Burden of Disease 15 Luo H. et al [ 27 ] 2016 Cameroon programs on adequacy of folate and vitamin B-12 intake Normative Women children 12–59 months National Health Surveys Biomarkers evaluated the baseline prevalence of inadequate intake and biochemical deficiency of these nutrients analysis of blood specimens High inadequate rates of folate and vitamin B-12 intake 16 Ramke J. et al [ 36 ] 2017 20 countries Cataract surgery number of people having operable cataract number of people with operated cataract Biomarker presenting visual acuity in the operated eye leading cause of blindness globally 17 Guerrero-Nunez S. et al [ 33 ] 2017 Chile Diabetes Mellitus Type 2 control diabetic patients prevalence rate diabetic patients participating in the health control program Biomarker Percentage of patients in metabolic control [HbA1c < 7%], according to the prevalence of Diabetes Mellitus type 2 at the national and regional level morbidity and mortality rate guaranteed pathologies 18 Nguhiu PK.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Prioritizing and coordinating micronutrient intervention programs Deficiencies in micronutrients contribute to excessive morbidity and mortality of young children globally 13 Travassos MA. et al [ 24 ] 2016 Ethiopia Immunization tetanus Haemophilus influenzae type b (Hib) Normative children aged 12–23 or 6–8 months Administrative Data vaccination cards and immunization clinic records household survey maternal recall Biomarkers Serosurveys Conflict in coverage rate of different sources 14 Ríos-Blancas MJ. et al 2016 Mexico Hypertension treatment The prevalence of hypertension Physical examination in national health survey biomarkers self-report of antihypertensive treatment Statistical methods two-step least squares method (MC2E) was used using instrumental variables (VI) instrumental variables One of leading causes of death Burden of Disease 15 Luo H. et al [ 27 ] 2016 Cameroon programs on adequacy of folate and vitamin B-12 intake Normative Women children 12–59 months National Health Surveys Biomarkers evaluated the baseline prevalence of inadequate intake and biochemical deficiency of these nutrients analysis of blood specimens High inadequate rates of folate and vitamin B-12 intake 16 Ramke J. et al [ 36 ] 2017 20 countries Cataract surgery number of people having operable cataract number of people with operated cataract Biomarker presenting visual acuity in the operated eye leading cause of blindness globally 17 Guerrero-Nunez S. et al [ 33 ] 2017 Chile Diabetes Mellitus Type 2 control diabetic patients prevalence rate diabetic patients participating in the health control program Biomarker Percentage of patients in metabolic control [HbA1c < 7%], according to the prevalence of Diabetes Mellitus type 2 at the national and regional level morbidity and mortality rate guaranteed pathologies 18 Nguhiu PK.…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the studies were carried out in order to use effective coverage for the assessment of specific program(s) or intervention(s). Some of these efforts have been done for preventive interventions such as immunization [ 24 26 ], programs to control micronutrients [ 27 , 28 ], cancer screening [ 29 ], and social support for women [ 30 ]. Also, there have been attempts to assess some treatment interventions for chronic diseases [ 22 , 31 33 ], hospital care for women and children [ 34 , 35 ] and cataract surgery [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study assessed the effectiveness of reminder sticker in reducing immunization dropout rate (52). The other study was on Biomarker sero surveys that emphasized the importance of objective serological biomarker measurement in determining vaccination coverage surveys (53). A technology based study that assessed the effect of text message reminders found no statistically signi cant association in improving immunization rates (54).…”
Section: Interventional Studies On Vaccination Programmentioning
confidence: 99%
“…The presence of antibody does not indicate how many doses of vaccine were received, or whether they were received in routine services or campaigns. For example, in a recent study in three districts of Ethiopia, postulated protective levels of tetanus antibodies were found in 67–94% of infants who had two documented doses of pentavalent vaccine and in 80–95% of infants with three documented doses, and even in those with only one documented dose, 40–80% had ‘protective’ levels . Attempts to correlate tetanus antibody prevalence with coverage of different vaccines will be further complicated in countries that have conducted campaigns using group A conjugate meningococcal vaccine having a tetanus toxoid carrier because this vaccine also stimulates tetanus immunity .…”
Section: Estimation Of Routine Vaccination Coveragementioning
confidence: 99%